2014
DOI: 10.1186/1471-2164-15-728
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for imputation to whole genome sequence using a single or multi-breed reference population in cattle

Abstract: BackgroundThe advent of low cost next generation sequencing has made it possible to sequence a large number of dairy and beef bulls which can be used as a reference for imputation of whole genome sequence data. The aim of this study was to investigate the accuracy and speed of imputation from a high density SNP marker panel to whole genome sequence level. Data contained 132 Holstein, 42 Jersey, 52 Nordic Red and 16 Brown Swiss bulls with whole genome sequence data; 16 Holstein, 27 Jersey and 29 Nordic Reds had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
125
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(154 citation statements)
references
References 28 publications
26
125
3
Order By: Relevance
“…This multi-breed reference population included 1147 sequenced animals with on average an 11-fold coverage, among which 311 Holstein bulls. All the individuals were used as reference because earlier studies showed that a multi-breed sequenced reference population can be beneficial for imputation accuracy, especially for SNPs with a low minor allele frequency (MAF) [4, 18, 19]. Polymorphic sites, including SNPs and short insertions and deletions (InDels), were identified for the 1147 individuals simultaneously using the multi-sample approach implemented in SAMtools’ mpileup along with BCFtools as described in Daetwyler et al [4].…”
Section: Methodsmentioning
confidence: 99%
“…This multi-breed reference population included 1147 sequenced animals with on average an 11-fold coverage, among which 311 Holstein bulls. All the individuals were used as reference because earlier studies showed that a multi-breed sequenced reference population can be beneficial for imputation accuracy, especially for SNPs with a low minor allele frequency (MAF) [4, 18, 19]. Polymorphic sites, including SNPs and short insertions and deletions (InDels), were identified for the 1147 individuals simultaneously using the multi-sample approach implemented in SAMtools’ mpileup along with BCFtools as described in Daetwyler et al [4].…”
Section: Methodsmentioning
confidence: 99%
“…We used a 15-fold cross-validation strategy described in several previous studies 33–35 . Ninety individuals were selected randomly from the sequenced reference population as a target population for each fold (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…These imputed genotypes were subsequently imputed to the whole genome sequence level using a multi-breed reference of 1,228 animals from run4 of the 1,000 Bull Genomes project (Daetwyler et al, 2014) and private data from Aarhus University. Data sets at different densities were prephased with BEAGLE4 r1274 (Browning and Browning, 2013) and imputations were done using IM-PUTE2 v2.3.1 (Howie et al, 2011), as suggested by Brøndum et al (2014). Genotypes for the QTL markers were then extracted from the whole genome sequence data.…”
Section: Genomic Predictionmentioning
confidence: 99%